ANALISIS EFEKTIVITAS JALUR EKSPEKTASI INFLASI DALAM MEKANISME TRANSMISI KEBIJAKAN MONETER DI INDONESIA: PENDEKATAN VECTOR AUTOREGRESSIVE (VAR) - Nurita Hutagalung (Universitas Negeri Medan, 2012)
Inflation expectations to be one of the main runway most economic agents in setting prices and wages, which in turn affect consumption and investment decisions. In relation to the aim of research is to look at the effectiveness of the path of inflation expectations by analyzing random kejutatan (shock) and the contribution of each variable to changes in another variable. The results of this study concluded that (1) all give each variable a random shocks to the other variables so as to achieve long-term equilibrium. This is shown by the results of the estimated IRF test on each variable, (2) all the variables together contribute to other variables as shown by the results of estimation VD test. From the estimation of inflation expectations can be concluded that monetary policy affects inflation.